IMAGE PROCESSING IN MOBILE DEVICES TO CLASSIFY PRESSURE INJURIES. - Mayara Tibes, Chris; Alvares Cherman, Everton; Mourão Alves de Souza, Vinícius; Martinez Évora, Yolanda Dora; Zem-Mascarenhas, Silvia Helena (Journal of Nursing UFPE / Revista de Enfermagem UFPE, 2016)
Objective: to develop an algorithm that helps classifying pressure injuries through image processing on mobile devices. Method: there are four main stages of development of the algorithm: building an image database; extracting images of the features; definition of a function that calculates the similarity between images; and recovery of the reference image most similar to the new image. Finally, a panel formed by nurses tested the accuracy of the system. Results: in the developed system, the user must upload a photo of the injury; the system will process that image, and, based on the processing algorithm implemented in the application, will make a suggestion of the likely stage of the injury. Conclusion: in the tests to verify the accuracy of the classifications through the algorithm, there were 100% of accuracy. Despite the limitations of the algorithm, the result of this research is encouraging and future studies should expand it.